Occurrence of Congenital Defects and their contributing Factors in Neonates - Dr. K. Manisha; Samiya Tabassum; P. Sthithapragna; Sadiya Naaz; Shaima (Asian Journal of Pharmaceutical Research and Development, 2025)
Objectives: To determine the common congenital abnormalities and estimate the underlying causes correlating with hereditary anomalies. Also, to calculate the possibility of congenital deformities and recognise the ways to prevent the birth defects in neonates. Methods: Multi-center future-oriented research ubiquity was executed at various hospitals in Karimnagar. The World Health Organization birth defect surveillance tool was employed to gather the demographic details of parents and neonates. We interviewed the mothers of newborns to analyze the exposure associated with birth defects. Results: Overall, 250 participants were covered in the inquiry.The candidates included were neonates. Out of 250, 6 had congenital malformation. The prevalence was established as 2.4%. Conclusion: The prevalence of birth defects was revealed to be 2.4%. The predictors aligned with the congenital anomalies were Sjogren’s syndrome, Rh incompatibility, Maternal history of left talipes foot, and Idiopathic causes.